AUTOWAVE SOLUTION APPROXIMATION IN LAMINAR FLAME MODELS - Evgeny N. Ladosha; Artem D. Pugachev; Denis S. Tsybmalov (Advanced Engineering Research)
A new algorithm for computing laminar flame in the combustible m ixture is suggested. The work differs from the known optimization algorithms in the accurate solution approximation method – the realistic form of not the temperature field itself, but of its derivative with respect to the self - simulated variable is postul ated. As a result, the effective model parameter determination procedure is simplified, and the approximation error remains at the acceptable value